I2/DMSO-Catalyzed Transformation of N-tosylhydrazones to 1,2,3-thiadiazoles - Li, Weiwei; Zhang, Jun; He, Jing; Xu, Liang; Vaccaro, Luigi; Liu, Ping; Gu, Yanlong (Frontiers in Chemistry, 2020)
An iodine/DMSO catalyzed selective cyclization of N-tosylhydrazones with sulfur without adding external oxidant was developed for the synthesis of 4-aryl-1,2,3-thiadiazoles. In this reaction, oxidation of HI by using DMSO as dual oxidant and solvent is the key, which allowed the regeneration of I2, ensuring thus the success of the synthesis. This protocol features by simple operation, high step-economy (one-pot fashion), broad substrate scope as well as scale-up ability.